2016
DOI: 10.1002/brb3.458
|View full text |Cite
|
Sign up to set email alerts
|

Influence of daily social stimulation on behavioral and physiological outcomes in an animal model of PTSD

Abstract: IntroductionWe have shown in previous work that acute episodes of predator exposure occurring in the context of chronic social instability produced PTSD‐like sequelae in rats. Our animal model of PTSD contained two components: (1) acute trauma, immobilization of rats in close proximity to a cat twice in 10 days, and (2) chronic social instability, 31 days of randomized housing of cage cohorts. Here we tested the hypothesis that daily social stimulation would block the development of the PTSD‐like sequelae.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 109 publications
(282 reference statements)
1
11
0
Order By: Relevance
“…Thymus involution is a well-accepted hallmark of stress, and we obtained a modest reduction in thymus mass in group housed animals. This finding is consistent with previously reported reductions in thymus mass in hamsters repeatedly exposed to a predator odor [39] and in rats subjected to cat odor or chronic, unstable group housing [40]. Our results are obviously just a single measure obtained after four weeks of stable housing conditions, and additional research would be necessary to determine a time course for the effect of housing or the effect of changing group composition in grouped animals on the thymus gland.…”
Section: Discussionsupporting
confidence: 92%
“…Thymus involution is a well-accepted hallmark of stress, and we obtained a modest reduction in thymus mass in group housed animals. This finding is consistent with previously reported reductions in thymus mass in hamsters repeatedly exposed to a predator odor [39] and in rats subjected to cat odor or chronic, unstable group housing [40]. Our results are obviously just a single measure obtained after four weeks of stable housing conditions, and additional research would be necessary to determine a time course for the effect of housing or the effect of changing group composition in grouped animals on the thymus gland.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, stimulation of social behavior or improving sense of well-being by enrichment of caging decreased corticosterone levels while counteracting thymus shrinkage in both mice and rats (Abou-Ismail and Mahboub, 2011; Seetharaman et al, 2016; Van Loo et al, 2004). A study in genetically engineered mice has provided direct evidence linking thymus gland size and function with corticosterone (Youn et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…We reported that rats exposed to a cat on two occasions, occurring within a 31-day period of chronic social instability, exhibited numerous behavioral and physiological outcomes which resemble the clinical symptoms of PTSD (for reviews see [67] & [68]). The most relevant observation from this work with regard to the current study is our finding that rats exhibit a long-term fear conditioned memory of the context and cue associated with the cat exposure component of chronic psychosocial stress [69]- [71] which persisted for at least 4 months [72].…”
Section: Introductionmentioning
confidence: 64%